Population dynamics of Lucilia eximia (Dipt., Calliphoridae) - Silva, ICR; Mancera, PFA; Godoy, WAC (Blackwell Verlag Gmbh, 2003)
The theoretical dynamics of experimental populations of Lucilia eximia was investigated as an attempt to understand its population biology. Specifically the population dynamics of L. eximia was analysed by means of a mathematical model that incorporates fecundity and survival as density-dependent demographic parameters in discrete time. The sensitivity of these parameters to changes in the magnitude was also investigated. The mathematical model applied to experimental populations of L. eximia predicts a theoretical one-point equilibrium for immatures. The population dynamics of L. eximia is compared to the dynamics of Chrysomya species and Cochliomyia macellaria.